Leptin signaling and its central role in energy homeostasis - Liu, Zhaoxun; Xiao, Tao; Liu, Hailan (Frontiers in Neuroscience, 2023)
Leptin plays a critical role in regulating appetite, energy expenditure and body weight, making it a key factor in maintaining a healthy balance. Despite numerous efforts to develop therapeutic interventions targeting leptin signaling, their effectiveness has been limited, underscoring the importance of gaining a better understanding of the mechanisms through which leptin exerts its functions. While the hypothalamus is widely recognized as the primary site responsible for the appetite-suppressing and weight-reducing effects of leptin, other brain regions have also been increasingly investigated for their involvement in mediating leptin's action. In this review, we summarize leptin signaling pathways and the neural networks that mediate the effects of leptin, with a specific emphasis on energy homeostasis.